2016
DOI: 10.4209/aaqr.2015.05.0325
|View full text |Cite
|
Sign up to set email alerts
|

Dust Induced Changes in Ice Cloud and Cloud Radiative Forcing over a High Altitude Site

Abstract: Aerosol-cloud interaction is the subject of considerable scientific research, due to the importance of clouds in controlling climate. In the present study, three years (2011)(2012)(2013) satellite observations are used to investigate the aerosol indirect effect (AIE) over Dehradun. The low values of Angstrom exponent (α) during March-July are attributed to the loading of dust-like coarse particles in the atmosphere, whereas the analysis of aerosol type and Spectral Radiation Transport Model for Aerosol species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…However, the aerosol effects on ice clouds have been difficult to constrain due to numerous controlling factors. For example, Huang et al (2006) and W. C. showed that the existence of dust aerosols significantly lower cloud optical thickness (COT) and ice water path (IWP) of ice clouds compared with pristine conditions, whereas a number of studies (Ou et al, 2009;Patel & Kumar, 2016;Tesche et al, 2016) reported a significant increase in COT and/or IWP with an increase in dust aerosols or aircraft exhaust. C. Wang et al, 2015).…”
Section: Citationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the aerosol effects on ice clouds have been difficult to constrain due to numerous controlling factors. For example, Huang et al (2006) and W. C. showed that the existence of dust aerosols significantly lower cloud optical thickness (COT) and ice water path (IWP) of ice clouds compared with pristine conditions, whereas a number of studies (Ou et al, 2009;Patel & Kumar, 2016;Tesche et al, 2016) reported a significant increase in COT and/or IWP with an increase in dust aerosols or aircraft exhaust. C. Wang et al, 2015).…”
Section: Citationmentioning
confidence: 99%
“…However, the aerosol effects on ice clouds have been difficult to constrain due to numerous controlling factors. Moreover, limited available studies have shown contradicting results (Chylek et al, 2006;Huang et al, 2006;Jiang et al, 2008;Ou et al, 2009;Patel & Kumar, 2016;Su et al, 2011;Tesche et al, 2016;W. C. Wang et al, 2015).…”
Section: Citationmentioning
confidence: 99%
See 1 more Smart Citation
“…ACI studies often use satellite retrievals to take advantage of their global coverage, but satellites have been unable to measure the CCN. Nevertheless, the aerosol optical parameters such as aerosol optical depth (AOD) and aerosol index (AI) are commonly used as proxies for CCN in previous studies (Gryspeerdt & Stier, 2012;Patel et al, 2017Patel et al, , 2019Patel & Kumar, 2016;Quaas et al, 2008Quaas et al, , 2009Rosenfeld, 2008). However, all these proxies are crude tools and suffer from various issues such as aerosol swelling, lack of vertical information, cloud contamination, uncertainty in size distribution and solubility, and more (Rosenfeld et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the south Asian context, field observations conducted near the Himalayan foothills in India indicated the presence of elevated transported dust (Padmakumari et al, 2013) and large spatial variation in IN concentrations (Patade et al, 2014). Dust-induced microphysical responses in ice cloud formation have been studied over India using general circulation models (GCMs; Hazra, 2013) and satellite observations (Patel & Kumar, 2016). However, the response of precipitation to dust-induced ice cloud modification and its meteorological dependency is largely unknown.…”
Section: Introductionmentioning
confidence: 99%